PEMINDAHAN RUMAH IBADAH DAN FASILITAS UMUM AKIBAT PENGADAAN TANAH UNTUK PEMBANGUNAN JALAN TOL BERDASARKAN UNDANG - UNDANG NOMOR 2 TAHUN 2012 TENTANG PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM - F. Kristifani Haryanto; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2019)
Serpong-Cinere Toll Road with a length of 10.14 km is part of the Jakarta Outer Ring Road 2 (JORR II) which connects South Tangerang with Depok City that crosses several regions, such as Jombang, Ciputat, Pamulang, Pondok Cabe and Cinere. The construction of this toll road was carried out based on Law Number 2 of 2012 concerning Land Procurement for Development for Public Interest. In the construction of this toll road, it certainly requires land from the people who live around the development toll road so that toll road operators must provide compensation. Compensation for land and buildings for residents is given in the form of money, while compensation for houses of worship and other public facilities is provided in the form of replacement land. Is the mechanism for transferring places of worship and public facilities has been carried out in accordance with Law Number 2 of 2012? Author using normative research methods and doing research by interviewing toll road operators as supporting data. The results of the study indicate that the mechanism for moving houses of worship and public facilities has been carried out according to Law Number 2 of 2012 and other law and regulation, namely Law Number 41 of 2004 concerning Endowments.